CASE SERIES AND REVIEW ON THE MANAGEMENT OF BLADDER CALCULI CAUSED BY IUD MIGRATION - Utama, Yohanes Dona Christi; Daryanto, Besut; Budaya, Taufiq Nur (Indonesian Urological Association, 2024)
Objective: Comparing two cases of the management of bladder calculi caused by Intra Uterine Device (IUD) migration with other similar cases worldwide. Case(s) Presentation: A forty-eight-year-old woman diagnosed by Abdominal Non-contrast Computed Tomography (NCCT), already done IUD extraction through the bladder approach also hysteroscopy to evaluate the position from the womb side, and continued with the stone removal by vesicolithotripsy. The second case revealed a bladder stone with IUD tail presence based on Kidney Ureter Bladder (KUB), performed vesicolithotomy, and IUD was found attached to the stone. Both patients’ conditions improved after surgeries. IUD migration into the bladder causes perforation, stone formation, and Urinary Tract Infection (UTI). NCCT, KUB, and Ultrasonography can be used as imaging modalities for initial screening when IUD migration is suspected. Discussion: The managements consist of open cystolithotomy, transurethral grasping forceps, or minimally invasive laparoscopy. Open and laparoscopic surgery should be considered for the IUD removal with partial penetration due to vesicouterine fistula and high-risk stone removal, especially for the large stone with IUD embedded inside. Conclusion: Minimally invasive methods are efficient, safe, and frequently preferred for the bladder stone caused by IUD migration. Keywords: Bladder stone, IUD, migration.